The Effectiveness of Using Rizky Ridho as a Brand Ambassador for G-SHOCK in Social Media Communication among the East Java Community - Jerryco Shantika; Gatut Priyowidodo; Felicia Goenawan (Journal of Content and Engagement, 2025)
This study examines the effectiveness of using Rizky Ridho as a brand ambassador for G-SHOCK in social media communication among the East Java community. The increasing use of public figures in digital communication highlights the need to evaluate how effectively they convey brand messages and engage audiences. This research aims to measure the effectiveness of Rizky Ridho as G-SHOCK’s brand ambassador using the VisCAP model, which consists of Visibility, Credibility, Attraction, and Power. A quantitative descriptive approach was employed through a survey method. Data were collected by distributing online questionnaires to 100 respondents in East Java who were aware of Rizky Ridho’s role as a brand ambassador for G-SHOCK. The results show that Rizky Ridho is perceived as an effective brand ambassador overall. The indicators of visibility and credibility received the highest evaluations, indicating strong brand recognition and trust among audiences. Meanwhile, attraction and power were rated as effective but showed relatively lower influence. These findings suggest that while Rizky Ridho supports brand communication by enhancing awareness and credibility, additional communication efforts are needed to strengthen audience influence. This study concludes that the use of a relevant public figure can support effective communication strategies on social media.